Paradox of White Collar Crime and Fraud in Banking: Critical Analysis of Agency Theory and Gone Theory - Nanang Shonhadji (Universitas PGRI Madiun, 2020)
ABSTRACT This study aims to criticize the causal relationship between agency theory and GONE theory with Habermas's radical humanist paradigm. Qualitative research methods and in-depth interviews with informants were used in this study. The results of the study inform that agents can be free from pragmatic agency theory through three forms of exemption. The first liberation proposed is to reduce one's greediness. The second release was carried out through an ethical and moral customer due diligence program. The liberation of the third form aims to reduce the rationality of economic relations that tend to prioritize the needs of individuals. ABSTRAK Penelitian ini bertujuan untuk mengkritisi hubungan kausalitas antara agency theory dan GONE theory dengan paradigma radical humanis Habermas. Metode penelitiaan kualitatif dan wawancara mendalam dengan informan digunakan dalam penelitian ini. Hasil penelitian menginformasikan bahwa agent dapat terbebaskan dari penerapan agency theory yang bersifat pragmatis melalui tiga bentuk pembebasan. Pembebasan pertama yang diusulkan adalah mereduksi sifat serakah pada diri seseorang. Pembebasan bentuk kedua dilakukan melalui program customer due diligence yang beretika dan bermoral. Pembebasan bentuk ketiga bertujuan untuk mereduksi adanya rasionalitas hubungan ekonomi yang cenderung mementingkan kebutuhan individu.